A Dynamic Traffic-Aware Duty Cycle Adjustment MAC Protocol for Energy Conserving in Wireless Sensor Networks. (26th February 2012) - Hsu, Tz-Heng; Kim, Tai-Hoon; Chen, Chao-Chun; Wu, Jyun-Sian
Abstract : Wireless sensors are battery-limited sensing and computing devices. How to prolong the lifetime of wireless sensors becomes an important issue. In order to reduce the energy consumptions when nodes are in idle listening, duty-cycle-based MAC protocols are introduced to let node go into sleep mode periodically or aperiodically. The long duty cycle makes sensors increase the transmission throughput but consumes more energy. The short duty cycle makes sensors have low energy consumption rate but increases the transmission delay. In this paper, a dynamic traffic-aware MAC protocol for energy conserving in wireless sensor networks is proposed. The proposed MAC protocol can provide better data transmission rate when sensors are with high traffic loading. On the other hand, the proposed MAC protocol can save energy when sensors are with low traffic loading. Simulation results show that the proposed protocol has better data throughput than other duty-cycle-based MAC protocols, for example, S-MAC and U-MAC. We also developed a set of comprehensive experiments based on the well-known OMNET++ simulator and revealed that our proposed TA-MAC performs significantly outstanding than related schemes under various situations.